(X-3)(Y+7)=0

Simple and best practice solution for (X-3)(Y+7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-3)(Y+7)=0 equation:


Simplifying
(X + -3)(Y + 7) = 0

Reorder the terms:
(-3 + X)(Y + 7) = 0

Reorder the terms:
(-3 + X)(7 + Y) = 0

Multiply (-3 + X) * (7 + Y)
(-3(7 + Y) + X(7 + Y)) = 0
((7 * -3 + Y * -3) + X(7 + Y)) = 0
((-21 + -3Y) + X(7 + Y)) = 0
(-21 + -3Y + (7 * X + Y * X)) = 0
(-21 + -3Y + (7X + XY)) = 0

Reorder the terms:
(-21 + 7X + XY + -3Y) = 0
(-21 + 7X + XY + -3Y) = 0

Solving
-21 + 7X + XY + -3Y = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 7X + XY + 21 + -3Y = 0 + 21

Reorder the terms:
-21 + 21 + 7X + XY + -3Y = 0 + 21

Combine like terms: -21 + 21 = 0
0 + 7X + XY + -3Y = 0 + 21
7X + XY + -3Y = 0 + 21

Combine like terms: 0 + 21 = 21
7X + XY + -3Y = 21

Add '3Y' to each side of the equation.
7X + XY + -3Y + 3Y = 21 + 3Y

Combine like terms: -3Y + 3Y = 0
7X + XY + 0 = 21 + 3Y
7X + XY = 21 + 3Y

Reorder the terms:
-21 + 7X + XY + -3Y = 21 + 3Y + -21 + -3Y

Reorder the terms:
-21 + 7X + XY + -3Y = 21 + -21 + 3Y + -3Y

Combine like terms: 21 + -21 = 0
-21 + 7X + XY + -3Y = 0 + 3Y + -3Y
-21 + 7X + XY + -3Y = 3Y + -3Y

Combine like terms: 3Y + -3Y = 0
-21 + 7X + XY + -3Y = 0

The solution to this equation could not be determined.

See similar equations:

| 6(5-2y)-5(y+3)= | | 5x-(x-18)=6-2(x+15) | | x*(x+1)(x+2)(x+3)=0.5625 | | 4(2+3)-2y= | | X^3-3x^2+x+1=0 | | -16-8(2a+3)=23-2a | | 4(2+3)-2y=3(4y+3) | | -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 | | y=40ln(3x+8) | | 12-2u=8u+45 | | 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 | | 5/x+6=17/x | | x+2y+3z=1 | | 0.2y=3y | | 83-3x=10x+8 |

Equations solver categories